How GenAI-supported multi-modal presentations benefit students with different motivation levels: Evidence from digital storytelling performance, critical thinking awareness, and learning attitude - Hui-Chun Chu, Yi-Chun Lu, Yun-Fang Tu (Educational Technology & Society)
This study guided 97 undergraduates using generative artificial intelligence (GenAI) to conduct multimodal digital storytelling (M-DST) learning activities. Furthermore, the study examined the differences in M-DST ability and critical thinking awareness among undergraduates with different levels of learning motivation and their perceptions of this learning approach. The study demonstrated that the high learning motivation level (HLM) group exhibited significantly superior M-DST performance compared to the low learning motivation level (LLM) group, particularly regarding story structure, accuracy, completeness, appearance, creativity, and interactivity. Furthermore, the HLM group demonstrated a significantly higher level of critical thinking awareness than the LLM group. Regarding learning attitudes, the HLM group demonstrated a greater interest in and receptivity of using GenAI for artistic creation, and a higher curiosity about course satisfaction and AI technology. Irrespective of learning motivation, undergraduates rated GenAI and traditional digital storytelling as being similarly interesting. Nevertheless, some undergraduates stated their concerns regarding the possibility of over-reliance on AI, which might lead to poor learning outcomes or even ethical problems. Some of them highlighted the problems encountered when using AI, such as inaccurate information and challenges in expressing emotions. Despite these issues, most of them considered that mastering AI technology as well as critical thinking and creativity are essential competences nowadays. They also emphasized the importance of collaborating with AI to complete tasks in a more efficient and effective manner. Based on these findings, several recommendations and some guidance are provided to educators for designing and implementing GenAI-based teaching and learning activities.